An Easy Death - Harris, Charlaine (New York : Saga Press, 2018)
"In this alternate history where the US has collapsed during WWII and been split into five different countries, including the southwestern territory of Texoma, Gunnie Lizbeth Rose is hired by two Russian magicians to find Alex Karkarov, and his family, as they need to bring them back to the New Russia-held west coast states for the blood of the Karkarov line is healing to the ruling family. Little do the magicians know that Lizbeth is Karkarov's daughter, and that she killed him"--
Publishers Weekly
Kirkus Reviews
Booklist
Library Journal
Adult
Keywords: Magic -- Fiction; Wizards -- Fiction; Texas -- Fiction; Alternative histories (Fiction)